Molecular Characterization of Retinoic Acid Receptor CgRAR in Pacific Oyster (Crassostrea gigas) - Jin, Kaidi; Jin, Qianqian; Cai, Zhongqiang; Huang, Baoyu; Wei, Lei; Zhang, Meiwei; Guo, Wen; Liu, Yaqiong; Wang, Xiaotong (Frontiers in Physiology, 2021)
RA signaling pathways mediated by retinoic acid receptors (RARs) is essential for many physiological processes such as organ development, regeneration and differentiation in animals. Recent studies reveal that RARs identified in several mollusks, including Pacific oyster Crassostrea gigas, have different function mechanism compared with that in chordates. In this report, we identified the molecular characteristics of CgRAR to further explore the mechanism of RAR in mollusks. RT-qPCR analysis show that CgRAR have a higher expression level in the haemocytes and gonads, indicating CgRAR may play roles in the processes of developmental and metabolism. The mRNA expression level of both CgRAR and CgRXR were analyzed by RT-qPCR after inject with RA. Elevated expression of CgRAR and CgRXR were detected upon ATRA exposure. Finally, according to the results of yeast two hybrid assay and co-immunoprecipitation analysis, CgRAR and CgRXR can interact with each other through the C-terminal region. Taken together, our results suggest that CgRAR show relative higher expression level in gonads and haemocytes. ATRA exposure up-regulate the expression of CgRAR and CgRXR. Besides, CgRAR can interact with CgRXR to form heterodimer complex.